Kidney Cell Cycle Arrest and Cardiac Biomarkers and Acute Kidney Injury Following Angiography: The Prevention of Serious Adverse Events Following Angiography (PRESERVE) StudyPlain Language Summary - Raghavan Murugan; Monique Y. Boudreaux-Kelly; John A. Kellum; Paul M. Palevsky; Steven Weisbord (Kidney Medicine, 2023)
Rationale & Objective: Recent studies in patients with chronic kidney disease (CKD) indicate that most cases of contrast-associated acute kidney injury (CA-AKI) are mild and are not associated with elevation in kidney injury biomarkers. We used highly sensitive kidney cell cycle arrest and cardiac biomarkers to assess the risk of CA-AKI and major adverse kidney events in patients with CKD undergoing angiography. Study Design: A retrospective study. Setting & Participants: A subset of 922 participants from the Prevention of Serious Adverse Events following Angiography trial. Predictors: Pre- and postangiography urinary tissue inhibitor of matrix metalloproteinase [TIMP]-2 and insulin growth factor binding protein [IGFBP]-7 were measured in 742 subjects, and plasma β natriuretic peptide (BNP) and high-sensitivity C-reactive protein (hs-CRP), and serum troponin (Tn) in 854 participants using samples obtained 1-2 hours before and 2-4 hours after angiography. Outcomes: CA-AKI and major adverse kidney events. Analytical Approach: We fitted logistic regression to examine association and area under the receiver operating characteristic curves for risk prediction. Results: There were no differences in postangiography urinary [TIMP-2]•[IGFBP7], plasma BNP, serum Tn, and hs-CRP concentrations among patients with and without CA-AKI and major adverse kidney events. However, higher pre- and postangiography median plasma BNP (pre: 200.0 vs 71.5, pg/mL, P = 0.05; post: 165.0 vs 81 pg/mL, P = 0.02); serum Tn (pre: 0.03 vs 0.01, ng/mL, P < 0.001; post, 0.04 vs 0.02, ng/mL, P = 0.01); and hs-CRP (pre: 9.55 vs 3.40 mg/L, P = 0.01; post: 9.90 vs 3.20 mg/L, P = 0.002) concentrations were associated with major adverse kidney events, although their discriminatory capacity was only modest (area under the receiver operating characteristic curves <0.7). Limitations: Most participants were men. Conclusions: Most mild CA-AKI cases are not associated with urinary cell cycle arrest biomarker elevation. Significant elevation in preangiography cardiac biomarkers may reflect patients with more significant cardiovascular disease that may predispose to poor long-term outcomes independent of CA-AKI status.